Korelasi antara Penguasaan Mufradat, Bi'ah Lugawiyyah, dan Mahārah al-Kalām Santri Al-Izzah Leadership School Batu - Shobirin, Abdurrahman (Study Program of Arabic Language Teaching, 2021)
This research is a correlational study that looks for the relationship between arabic vocabulary mastery, language environment, and arabic speaking skills among students of al-Izaah Leadership School Sumberjo, Batu. The problems found are as follows: (1) The lack of knowledge of students' vocabulary in communicating using Arabic, (2) The number of students who enter the language court is due to Javanese and language that is not by the nature of education, (3) several students are hesitant to use the vocabulary that has been given and nervous when evaluating orally. The results showed that there was a significant relationship between arabic vocabulary mastery, language environment, and arabic speaking skills because the significance value (Sig.) 0.011 was smaller than 0.05 (0.011 < 0.05), and t count was 5.597 greater than F. table N = 25 with a value of 4.240 (5.597 > 4.240). The contribution of arabic vocabulary mastery is 32.3%, and the gift of the language environment is 0.2%. The low contribution of these two variables impacts the soft arabic speaking skills produced among students of al-Izzah Leadership School Sumberjo, Batu, which is 33.7%. The more negligible contribution to arabic vocabulary mastery and the language environment, the resulting arabic speaking skills become smaller.